Impact of Periampullary Diverticulum on ERCP Performance: A Matched Case-Control Study - Juan E. Corral; Omar Y. Mousa; Paul T. Kröner; Victoria Gomez; Frank J. Lukens (Clinical Endoscopy, 2019)
Background/Aims Periampullary diverticulum (PAD) is frequently encountered during endoscopic retrograde cholangiopancreatography (ERCP) and has been associated with stone formation in the bile duct. The effects of PAD on the ERCP procedure have been often debated. We aimed to compare the therapeutic success of ERCP between patients with PAD and matched controls. Methods We reviewed all ERCPs with findings of PAD in a national database (n=1,089) and compared them with age- and gendermatched controls in a 1:3 fashion (n=3,267). Demographics, endoscopic findings, visualization of main structures, and therapeutic success rates were compared between groups. Secondary analysis compared PAD cases and controls who had gallstone disease. Results The average cohort age was 68.4±14.3 years and 55.1% were male. ERCP success was similar in both groups, and no significant inter-group differences were found in the multivariate analysis. The presence of PAD did not affect the rates of sphincterotomy or visualization of main biliary structures. Secondary analysis showed similar success rates for gallstone removal between patients with PAD and controls. Conclusions PAD may not be considered a hinderance to ERCP success. Further research is needed to determine the best approach to cannulate the ampulla and provide endoscopic therapy for different subtypes of PAD.